Digestibilidade aparente dos nutrientes e características físico-químicas das fezes de equídeos alimentados com feno de tifton - Brito, Jéssica de Carvalho (2016)
The horses and donkeys are different species of horses that have physiological characteristics that need to be understood for better accomplishment of food management and food nutrients utilization Thus, the objective was to compare and evaluate the voluntary food intake and the implications on the physico-chemical characteristics of the stool, production of short chain fatty acids and apparent digestibility of a diet consisting of hay Tifton 85 in equine and asinine species. Twenty animals were used, ten quarter mile race horses and ten Pêga breed asses, distributed in a completely randomized design with two treatments of ten repetitions, being the animal the experimental unit. It is considered as treatments the two species analyzed. The animals were fed with Tifton 85 hay (85.72% DM, 12.88% CP, 73.74% NDF, 32.59% ADF and 2.25 Mcal GE/kg) at will, and it was evaluated the ability of voluntary intake. After six days of adaptation to experimental conditions, it was carried out four days of total stool collection. During the collection period, at 6h feces were collected for measurement of pH and buffering capacity (BC) as well as the color evaluation and stool consistency. During the collection period, the feces were homogenized for removal of a sample for the analyzes of dry matter (DM), crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF) and gross energy (GE). Digestibility coefficients were calculated for DM, CP, NDF, ADF and GE. Blood samples were collected on the last day of the digestibility trial, at 0, 3 and 6 h after feeding for analysis of short-chain fatty acids (SCFA), which were also analyzed in the stool. Donkeys showed consumption of 1.12 kg DM/BW statistically smaller (P <0.05) than equine (1.60 DM/BW). It was observed higher digestibility coefficients (P <0.05) to asses for DM (61.60%), CP (67,18%) NDF (54,17) and the ADF (50,00). There was no statistical difference for pH, color and consistency of stools among the species studied receiving diet composed only with bulky. The BC of donkeys was more efficient for BC6 (9.12 mmol/L) and BC5 (22.62 mmol/L) than horses (6.07 and 14.38 mmol/L, respectively). It was observed that donkeys produce more acetic acid (33.81 mmol/L) with a unique fodder diet, but they exhibit lower levels of this SCFA in the blood (1.00 mmol/L) compared to the horses (1.27 mmol/L), which shows less absorption of acetate in the cecum-colic region. The asses have consumption capacity of hay Tifton85 less than equine, but shows higher digestibility of nutrients and increased buffering capacity of short-chain fatty acids formed during fermentation.